Evaluation of the Effectiveness of the Use of Papaya Fruit Latex in Making Herbal Medicated Multinutrition Block as a Local Goat Feed Supplement - Pujaningsih, Retno Iswarin; Tampoebolon, Baginda Iskandar Moeda; Widiyanto, Widiyanto; Harjanti, Dian Wahju (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2018)
The use of papaya latex formulated with nitrogen supplementation and minerals in the form of multinutrition blocks that can pass through the rumen is expected to improve nutritional quality and feed digestibility. This study aims to evaluate the effectiveness of the use of fermented rice straw, papaya fruit latex and blood clamshell flour as a main raw material in the manufacture of multinutrition blocks plus herbal anthelmintic medicine (papaya fruit latex) on physical quality (texture, color, aroma, hardness), chemical quality (proximate composition and mineral content of Ca, P, Mg, Cu, Zn). Microbiological tests were carried out on total bacteria, Salmonella and Escherichia coli. The research design used was a completely randomized design with 4 treatment levels of papaya fruit administration and 4 replications. Data is processed statistically using ANOVA. The results of organoleptic physical quality analysis showed significant differences in the texture of the product given the highest papaya latex (0.007ml / kg). Chemical analysis of the product showed a quantitative increase in protein, although statistically the treatment did not show any significant differences. The results of the analysis of the microbiological quality of the product quantitatively showed that the resulting multinutrition block herbs were not contaminated with negative bacteria. It was concluded that multinutrition block herbs can be given to livestock as supplementary feed.